Wakaf Tunai dan Potensinya Kepada Pembangunan Sosio Ekonomi Ummah di Malaysia - Mohamad, M. H. (Universiti Sains Islam Malaysia, 2024)
Waqf is a charitable mechanism which is highly encouraged by Islam. Its benefits are not only limited to the continuous reward being granted to waqif(waqffounder) but it is also a great help in facilitating and creating a conducive environment to the society as a whole. Nevertheless, in Malaysia currently, we are facing an uphill task to maximize the usefulness of waqf instrument in enhancing the socio economic condition development process of the nation. If we reminisce to the history of Islam, it has been proven that waqf was an effective tool for the rulers in providing public amenities to its citizens and thus reducing the government expenditure. Nowadays, the legacy of waqf remains nothing hut a nostalgia. This predicament is attributed to a number of factors notably the limited perception among the society about the forms of waqf instruments and the lack of new systematic approach to popularize as well as to expand the role of waqf institutions. Therefore, this paper seeks 10 introduce the concept of cash waqf as the best approach to expand the role of waqf institutions and restore its effective function in enhancing the quality of life of society members.